Cognitive Impairment in the 3xTg-AD Mouse Model of Alzheimer's Disease is Affected by Aβ-ImmunoTherapy and Cognitive Stimulation - Alejandro R. Roda; Gisela Esquerda-Canals; Joaquim Martí-Clúa; Sandra Villegas (MDPI AG, 2020)
Clinical symptoms of Alzheimer's Disease (AD) include behavioral alterations and cognitive impairment. These functional phenotypes early occur in triple-transgenic (3xTg-AD) mice. Specifically, behavioral alterations are first detected when mice are at around 2.5 months old and cognitive impairment in between 3- and 5-month-old mice. In this work, the effect of chronic Aβ-immunotherapy on behavioral and cognitive abilities was tested by monthly administering the antibody fragment scFv-h3D6 to 3xTg-AD female mice from 5 to 9 months of age. An untreated group was used as a reference, as well as to attain some information on the effect of training during the longitudinal study. Behavioral and psychological symptoms of dementia (BPSD)-like symptoms were already evident in 5-month-old mice, in the form of neophobia and anxious-like behavior. The exploratory activity decreased over the longitudinal study, not only for 3xTgAD mice but also for the corresponding non-transgenic mice (NTg). Learning abilities of 3xTg-AD mice were not seriously compromised but an impairment in long-term spatial memory was evident at 5 months of age. Interestingly, scFv-h3D6-treatment affected the cognitive impairment displayed by 5-month-old 3xTg-AD mice. It is worth noting that training also reduced cognitive impairment of 3xTg-AD mice over the longitudinal study, suggesting that to properly quantify the isolated therapeutic potential of any drug on cognition using this model it is convenient to perform a prompt, age-matched study rather than a longitudinal study. In addition, a combination of both training and Aβ-immunotherapy could constitute a possible approach to treat Alzheimer's disease.